2018
DOI: 10.3389/fmicb.2018.02829
|View full text |Cite
|
Sign up to set email alerts
|

Pch Genes Control Biofilm and Cell Adhesion in a Clinical Serotype O157:H7 Isolate

Abstract: In a previous study, induction of the Escherichia coli serotype O157:H7 SOS response decreased csgD expression in the clinical isolate PA20 at 30°C but strongly induced genes in the horizontally transferred-DNA regions (HTR), including many known virulence regulators. To determine the role of HTR regulators in the control of csgD and curli, specific regulators were plasmid-expressed in the wild-type and mutant strains of PA20 and its biofilm-forming derivative, 20R2R. At 30°C, plasmid over-expression of the O1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…The activation of LEE and intimate cell attachment are well described properties of group 1 perC homologues, but the group 2 ( pchD ) and 3 ( pchE ) genes have been less well characterized [ 13 , 14 , 44 ]. This and previous studies have indicated that pchE functions in opposition to class 1 genes to manage cellular adhesion, likely in a temporal manner where pchE balances general cell adherence and motility prior to LEE activation and the initiation of stronger intimate contacts [ 38 , 42 ]. Earlier, we showed that PA20 expresses a low steady-state level of pchE that is reduced when prophage elements are induced [ 42 ].…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…The activation of LEE and intimate cell attachment are well described properties of group 1 perC homologues, but the group 2 ( pchD ) and 3 ( pchE ) genes have been less well characterized [ 13 , 14 , 44 ]. This and previous studies have indicated that pchE functions in opposition to class 1 genes to manage cellular adhesion, likely in a temporal manner where pchE balances general cell adherence and motility prior to LEE activation and the initiation of stronger intimate contacts [ 38 , 42 ]. Earlier, we showed that PA20 expresses a low steady-state level of pchE that is reduced when prophage elements are induced [ 42 ].…”
Section: Discussionsupporting
confidence: 58%
“…Our earlier studies showed that the expression of pchE reduced PA20 attachment to HEp-2 cells by repressing curli under conditions where the SOS response was not stimulated [ 38 ]. The findings also indicated that pchE controlled additional adhesins involved in cell attachment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations